An Analysis of Allowance Banking in the EU ETS - Aleksandar Zaklan; Denny Ellerman; Vanessa Valero (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The existence of some 2 billion unused EU Allowances (EUAs) at the end of Phase II of the EU s Emissions Trading System (EU ETS) has sparked considerable debate about structural shortcomings of the EU ETS. However, there has been a surprising lack of interest in considering the accumulation of EUAs in light of the theory of intertemporal permit trading, i.e. allowance banking. In this paper we adapt basic banking theory to the case of a linearly declining cap, as is common in greenhouse gas control systems. We show that it is perfectly rational for agents to decrease emissions beyond the constraint imposed by the cap initially, accumulating an allowance bank and then drawing it down in the interest of minimizing abatement cost over time. Having laid out the theory, we carry out a set of simulations for a reasonable range of key parameters, geared to the EU ETS, to illustrate the effects of intertemporal optimization of abatement decisions on optimal time paths of emissions and allowance prices. We conclude that bank accumulation as the result of intertemporal abatement cost optimization should be considered at least a partial explanation when evaluating the current discrepancy between the cap and observed emissions.
Keywords: Q54; D92; F18; 330